Structural Factors Responsible for Universal Health Coverage in Low- and Middle-Income Countries: Results From 118 Countries - Chhabi Lal Ranabhat; Chhabi Lal Ranabhat; Mihajlo Jakovljevic; Mihajlo Jakovljevic; Mihajlo Jakovljevic; Meghnath Dhimal; Chun-Bae Kim; Chun-Bae Kim; Chun-Bae Kim (Frontiers Media S.A., 2020)
Background: Demography, politics, economy, and governance appear to be the major structural factors for health and well-being. These factors have a significant role to play in achieving universal health coverage (UHC). The majority of previous studies did not highlight those factors. The aim of this study is to explore the basic structural factors (political stability, demography, gross national income, governance, and transparency) associated with a UHC index of low- and middle-income countries because for a long time there has be a stagnation achieving universal health coverage.Methodology: This study was a cross-sectional study applying multiple indices as variables. Low- and middle-income countries' selected indicators were the study variables. Data concerned the current political stability, sociodemographic status, gross national income (GNI), and governance status as independent variables and the UHC index of the countries as the dependent variable. Mean and standard deviations were used for the average values of the variables, a raw correlation was shown among variables and a hierarchical linear regression model was used for multi variate analysis.Results: Government health expenditure is 6% out of the total budget in upper middle countries (UMIC) and ~5% in lower middle countries (LMIC) and low-income countries (LIC), population below poverty line is more than 2-fold higher in LIC in comparison with high income countries, UHC index, and socio-demographic index (SDI) index is similar in LMIC and LIC and slightly higher in UMIC. There is a positive association between government health expenditure, governance index, stability index, the SDI index, and GNI per capita and a negative association between populations below poverty line with UHC index. According to our full regression analysis model, governance, stability, and SDI index were associated with a significantly increased UHC index by 0.33, 0.41, and 0.57 (p < 0.05).Conclusion: To achieve UHC, good governance, political stability, and demographic balance are prerequisites and addressing these factors would help to meet by 2030 across countries.